Hybrid Lead Halide Perovskites for Ultrasensitive Photoactive Switching in Terahertz Metamaterial Devices. Issue 32 (22nd June 2017) - Manjappa, Manukumara; Srivastava, Yogesh Kumar; Solanki, Ankur; Kumar, Abhishek; Sum, Tze Chien; Singh, Ranjan
Abstract : The recent meteoric rise in the field of photovoltaics with the discovery of highly efficient solar‐cell devices is inspired by solution‐processed organic–inorganic lead halide perovskites that exhibit unprecedented light‐to‐electricity conversion efficiencies. The stunning performance of perovskites is attributed to their strong photoresponsive properties that are thoroughly utilized in designing excellent perovskite solar cells, light‐emitting diodes, infrared lasers, and ultrafast photodetectors. However, optoelectronic application of halide perovskites in realizing highly efficient subwavelength photonic devices has remained a challenge. Here, the remarkable photoconductivity of organic–inorganic lead halide perovskites is exploited to demonstrate a hybrid perovskite–metamaterial device that shows extremely low power photoswitching of the metamaterial resonances in the terahertz part of the electromagnetic spectrum. Furthermore, a signature of a coupled phonon–metamaterial resonance is observed at higher pump powers, where the Fano resonance amplitude is extremely weak. In addition, a low threshold, dynamic control of the highly confined electric field intensity is also observed in the system, which could tremendously benefit the new generation of subwavelength photonic devices as active sensors, low threshold optically controlled lasers, and active nonlinear devices with enhanced functionalities in the infrared, optical, and the terahertz parts of the electromagnetic spectrum. Abstract : Remarkable photoconductivity of solution‐processed ultrathin perovskite film at terahertz frequencies is exploited for low‐power, high‐speed photoactive switching of the Fano resonance in a hybrid perovskite–metamaterial device. At higher pump fluences, a mode‐splitting behavior is observed, which manifests a phonon–metamaterial resonance coupling in the proposed system.